2018
DOI: 10.1101/285320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A direct glia-to-neuron natural transdifferentiation ensures nimble sensory-motor coordination of male mating behaviour

Abstract: Sexually dimorphic behaviours require underlying differences in the nervous system between males and females. The extent to which nervous systems are sexually dimorphic and the cellular and molecular mechanisms that regulate these differences are only beginning to be understood. We reveal here a novel mechanism to generate male-specific neurons in Caenorhabditis elegans, through the direct transdifferentiation of sex-shared glial cells. This glia-to-neuron cell fate switch occurs during male sexual maturation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…In terms of glia affecting sexual behavior, Grosjean et al (2008) demonstrated in male Drosophila melanogaster a glial aminoacid transporter regulated courtship and copulatory behavior toward other males. A more recent study showed that in male Caenorhabditis elegans, transdifferentiation occurs in glial cells that convert to neurons important for copulation (Molina-García et al, 2018). There abide a paucity of knowledge on how glia regulates sexual behavior, and given their critical role in regulating glutamate, future experiments can help elucidate the specific role of glia on glutamatergic signaling in sexual behavior.…”
Section: Glutamate Transporters and Rodent Male Sexual Behaviormentioning
confidence: 99%
“…In terms of glia affecting sexual behavior, Grosjean et al (2008) demonstrated in male Drosophila melanogaster a glial aminoacid transporter regulated courtship and copulatory behavior toward other males. A more recent study showed that in male Caenorhabditis elegans, transdifferentiation occurs in glial cells that convert to neurons important for copulation (Molina-García et al, 2018). There abide a paucity of knowledge on how glia regulates sexual behavior, and given their critical role in regulating glutamate, future experiments can help elucidate the specific role of glia on glutamatergic signaling in sexual behavior.…”
Section: Glutamate Transporters and Rodent Male Sexual Behaviormentioning
confidence: 99%
“…The nematode C. elegans provides distinct advantages for direct observation of neurological function in freely-behaving animals. They are small (<1 mm), exhibit short generational times, and have a compact and fully mapped connectome of 302 neurons in hermaphrodites and 387 in males 21 . Noninvasive optical measurements of neural activity can be made in living, behaving animals via genetically-encoded fluorescent calcium indicators such as GCaMP 22 , and genetic tools are available for rapid generation of mutants and transgenic strains for mechanistic studies [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Third, sexual dimorphism is prominent in the C. elegans nervous system. Compared to adult hermaphrodites, adult males have an additional 85 neurons, accounting for ∼20% of the nervous system ( Sulston and Horvitz, 1977 ; Sulston et al, 1980 ; Sammut et al, 2015 ; Molina-Garcia et al, 2018 ). Though progress has been made on the wiring of parts of the male nervous system ( Hall and Russell, 1991 ; Jarrell et al, 2012 ), a complete and comprehensive side-by-side comparison of high-quality male and hermaphrodite connectomes awaits.…”
Section: A Brief Background Of Caenorhabditis Elegans mentioning
confidence: 99%